Modifying the Biogents Sentinel Trap to Increase the Longevity of Captured Aedes aegypti. Issue 6 (24th July 2018) - Timmins, Daniel R; Staunton, Kyran M; Meyer, Dagmar B; Townsend, Michael; Paton, Christopher J; Ramírez, Ana L; Ritchie, Scott A
Abstract: Aedes aegypti (L.) (Diptera: Culicidae) is a vector of viruses causing dengue, Zika, chikungunya, and yellow fever and subsequently pose a significant global threat to public health. While sampling live mosquitoes is useful for surveillance purposes, most traps targeting Aedes kill captured mosquitoes. The Biogents Sentinel (BGS) trap, the gold standard for capturing Ae. aegypti, is one such trap. In our study, we modified the BGS trap to increase the survival of captured Ae. aegypti by replacing the trap's catch bag with a catch pot that protects mosquitoes from desiccation by airflow. A sucrose-soaked sponge or nucleic acid preservative card can also be placed inside the pot to enhance mosquito survival and augment arbovirus detection. These modifications to the BGS significantly increased the longevity of mosquitoes captured with weekly survivals of 93% in a semifield structure and 86% in the field. These high survival rates resulted in 3.5 times more alive Ae. aegypti captured weekly in the modified BGS compared to the original BGS, despite 40% lower overall catch rates. These cheap and simple trap modifications facilitate easier specimen identification as well as experiments requiring live field-collected samples such as virus detection from mosquito saliva and excreta.